Contemporary Thought on Nineteenth Century Socialism Volume IV, Anglo-Marxists. - Morgan, Kevin, 1961- (Milton : Routledge, 2021)
For historians of the international labour movement, the decades before 1914 were the golden age of Marxist thought. In this flowering of socialist thinking, Britain seemingly had no part, and the question has been asked instead: Why was there was no Marxism in Britain?' The selections in this volume confirm that Marxist ideas in Britain were not always pitched at the highest theoretical level. There are also examples of the reductionism to which leading exponents were sometimes prone. Nevertheless, there is also a richness and outspokenness across wide and varied themes that belies the caricature of arid economic determinism. Marxists believed they carried on the tradition of home-grown movements of struggle such as Chartism. They also identified with the new spirit of internationism whose ideas and personalities filled the pages of their periodicals. Behind such well-known names as William Morris, James Connolly and Tom Mann, a wider movement of contrarians remains to be discovered.
24 "Organised Labour. The Duty of the Trades Unions in Relation to Socialism", Commonweal, 14, 21 and 28 August 1886. -- 25 "Social Democracy and Industrial Organisation", Social Democrat, 15 April 1910. -- 26 "Prepare for Action", Industrial Syndicalist, July 1910, 31-54. -- 27 "Leadermania", Justice, 13 November 1897, 2. -- Part 6 Democracy and the state -- 28 "The Will of the Majority", in The Ethics of Socialism (London: Swan Sonnenschein, 1889), 120-128. -- 29 "Workmen's Jubilee Ode", Social Democrat, February 1897. -- 30 "After the Jubilee", Justice, 16 October 1897, 2.
Description based upon print version of record.
31 "The 'Monstrous Regiment' of Womanhood", in Essays in Socialism New and Old (London: Grant Richards, 1906), 276-279, 282-294.
OCLC-licensed vendor bibliographic record.
Keywords: Socialism -- Great Britain -- History -- 19th century; Great Britain -- Politics and government -- 19th century; HISTORY / General; HISTORY / Modern / 19th Century